3D Porous Scaffold-Based High-Throughput Platform for Cancer Drug Screening - Yang Zhou; Gillian Pereira; Yuanzhang Tang; Matthew James; Miqin Zhang (MDPI AG, 2023)
Natural polymer-based porous scaffolds have been investigated to serve as three-dimensional (3D) tumor models for drug screening owing to their structural properties with better resemblance to human tumor microenvironments than two-dimensional (2D) cell cultures. In this study, a 3D chitosan-hyaluronic acid (CHA) composite porous scaffold with tunable pore size (60, 120 and 180 µm) was produced by freeze-drying and fabricated into a 96-array platform for high-throughput screening (HTS) of cancer therapeutics. We adopted a self-designed rapid dispensing system to handle the highly viscous CHA polymer mixture and achieved a fast and cost-effective large-batch production of the 3D HTS platform. In addition, the adjustable pore size of the scaffold can accommodate cancer cells from different sources to better mimic the in vivo malignancy. Three human glioblastoma multiforme (GBM) cell lines were tested on the scaffolds to reveal the influence of pore size on cell growth kinetics, tumor spheroid morphology, gene expression and dose-dependent drug response. Our results showed that the three GBM cell lines showed different trends of drug resistance on CHA scaffolds of varying pore size, which reflects the intertumoral heterogeneity across patients in clinical practice. Our results also demonstrated the necessity to have a tunable 3D porous scaffold for adapting the heterogeneous tumor to generate the optimal HTS outcomes. It was also found that CHA scaffolds can produce a uniform cellular response (CV < 0.15) and a wide drug screening window (Z' > 0.5) on par with commercialized tissue culture plates, and therefore, can serve as a qualified HTS platform. This CHA scaffold-based HTS platform may provide an improved alternative to traditional 2D-cell-based HTS for future cancer study and novel drug discovery.